2022
DOI: 10.1038/s41598-022-21362-6
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous bacteria as an alternative for promoting recycled paper and cardboard mill wastewater treatment

Abstract: The present study aimed to investigate indigenous bacteria possibility in recycled paper and cardboard mill (RPCM) wastewater treatment through the isolation and identification of full-scale RPCM indigenous bacteria. The molecular characterization of the isolated bacteria was performed by 16S rRNA gene sequencing. Klebsiella pneumoniae AT-1 (MZ599583), Citrobacter freundii AT-4 (OK178569), and Bacillus subtilis AT-5 (MZ323975) were dominant strains used for RPCM wastewater bioremediation experiments. Under opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…It is worth mentioning that maximum COD and BOD reduction is obtained by inoculants (MI‐1 and MI‐2) containing Bacillus subtilis along with other microbial species. Several studies have reported that microbial consortia including B. subtilis can significantly degrade organic loads 64‐67 . The BOD and COD removal efficiency demonstrated by the inoculants, although encouraging, were not very significant when compared to CT.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…It is worth mentioning that maximum COD and BOD reduction is obtained by inoculants (MI‐1 and MI‐2) containing Bacillus subtilis along with other microbial species. Several studies have reported that microbial consortia including B. subtilis can significantly degrade organic loads 64‐67 . The BOD and COD removal efficiency demonstrated by the inoculants, although encouraging, were not very significant when compared to CT.…”
Section: Resultsmentioning
confidence: 91%
“…Several studies have reported that microbial consortia including B. subtilis can significantly degrade organic loads. [64][65][66][67] The BOD and COD removal efficiency demonstrated by the inoculants, although encouraging, were not very significant when compared to CT. This might be a consequence of the fact that raw wastewater in the control bioreactor also contains some ingenious bacteria (e.g.…”
Section: Removal Of Organic Load (Cod and Bod)mentioning
confidence: 90%
“…27,28 B. subtilis, also known as grass or hay bacillus is a rod shaped, heat-resistant bacteria found in soil and gastrointestinal tract of humans or ruminants. 29,30 It is one of the most efficient bacteria in treatment of wastewater. 31,32 B. subtilis is an aerobic decomposer which is known to degrade heavy metals and reduce toxicity of water.…”
Section: Introductionmentioning
confidence: 99%